ESTIMACIÓN DE LA TEMPERATURA UMBRAL Y DE LOS REQUERIMIENTOS TÉRMICOS NECESARIOS PARA EL DESARROLLO DE PUPAS DE TRICHOPODA GIACOMELLU (DIPTERA: TACHINIDAE) - Liuesthróm, G. (Acta Entomológica Chilena, 2022)
. T. giacomellii pupae were placed at the following constant temperatures (+- PC): 5; 11; 13; 15; 16; 18; 24; 27 and 30°C and 70% relative humidity. The effect o f temperature on the survivorship and the rate of development was estimated. At 5°C there were no survivors, and at 1 PC survivorship was 17%. From I3°C up to 30°C survivorship fluctuated around the mean valué 97,14% (no significant difference). The development rate was well fitted by the linear regression equation: y = -0.03326 + 0.00423 x (r2 = 0.9859), and by extrapolation it was calculated the temperature threshold (7.87°C). The heat units accumulation required for pupal development fluctuated with no significant difference between 200.49 °C-days (mínimum valué at 13°C) and 258.04 °C-days (máximum valué at 24°C), around the constant heat unit accumulation (235.57 °C) calculated from the slope of the regression equation.